Semantics of the Qur’ānic lexeme ’ummī. - Rybalkin., V. (Journal of Oriental Studies, 2016)
The relative adjective ‘’ummī’ appears six times in the Qur’ān. Since it has attracted varying interpretations both in Muslim exegesis and foreign translations of the Qur’ān, its use in every context is analyzed. For most Muslim authors the word ’ummī denotes Muhammad’s illiteracy, the fact that proves the greatest miracle of the Book inasmuch it was revealed directly to the mind of the Prophet who didn’t know how to read or to write. Nevertheless Muhammad’s illiteracy is not regarded with certainty by most Western orientalists, nor even by some Muslim authors. Furthermore, the philological-historical examination of the term ’ummī and its derivatives does not confirm the popular interpretation of ’ummī, which focuses exclusively on illiteracy. The given Qur’ānic context determines two preferable semantic fields for understanding the meaning of the word ’ummī in the relevant passages of the Muslim Hole Scripture: 1) the people who don’t know the Hole Scripture perfectly or the polytheists of the pre-Islamic period without any revealed book; 2) the Prophet’s origin from the common folk (’umma). These two principal meanings should be accurately rendered in the foreign translations of the Qur’ān.